Krisis Ekonomi Krisis Politik Dunia Dan IHSG - Vidyarto Nugroho; Ishak Ramli (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2016)
The global economic crisis of 2008-2010 had an impact on the global economic slowdown. Plus the political crisis in the countries of the Middle East region called the Arab Spring had become the centre of world attention because it also lowers economic conditions and corporate America and in other developing countries. By using daily data price of crude oil, the price of gold and exchange rates as well Rp/USD IDX Composite Index from the year 2010 - 2012, tested the impact of crude oil prices, global gold prices on the Stock Exchange Composite Index. The result was at the time of the global economic and political crisis in oil prices and the world gold price positively affects JCI opposed to when normal conditions. When the economic crisis plus the political crisis led to the oil price increases, the share price (CSPI) on the Stock Exchange also increased. Funds drawn investors from investing in the United States and other developing countries is invested in Indonesia so that stock prices rise along with oil prices and gold prices. While the exchange rate negatively affects Rp/USD JCI Stock Exchange, as a stronger rupiah lead JCI Stock Exchange also increased